PRODUCT DEVELOPMENT ON CUSTOMER PERCEPTION TOWARDS CASH FLOW PROJECTION FOR BAKERY IN BANDUNG - Christian, Han
This research is about making a new product for bakery industry in Bandung to fit in the market, based on customer perception, the conjoint analysis and cash flow projection also economic feasibility analysis. These research conducted in Bandung and Cimahi area with the respondents criteria has the 15-34 age range as the respondent and lives or stay in Bandung or Cimahi area. The respondent's result of this research are 136, but because the research scope and limitations, only 123 respondents that valid for this research. Based on the conceptual framework in this research, an online questionnaire was conducted to get customer perception information and will be followed by a combination ranking questionnaire to do the conjoint analysis. Factors from the conceptual framework, company data and the previous findings are used to design the questionnaire. Customer perception information is being used for searching the right factors to creating the best bakery product with suitable price and strategic location that fit with customers perception also knowing the customer's order frequency, based on customers perception. Customers perception factors findings tested with conjoint analysis and will produce some combination of the attribute combination for the product, the optimal price for the product and the optimal location for sold the product, these factors plus frequency buying the product will be used to make cash flow projection. This research will produce 18 cash flow projection scenario for 3 years, the combination of the number of stores, product price tag and the number of order frequency. This 18 cash flow projection scenario will be tested using an economic feasibility analysis to test the feasibility. Economic feasibility test consists of net present value, internal rate of return, payback period and sensitivity analysis. the cash flow that pas all of the economic feasibility test mean good to executed in the real situation. Based on the findings from this research is that the most important factor to consider in developing a new bakery product in Bandung is the location where the product is sold, the second factor is price and the last is product attribute. From the cash flow projection analysis from 18 cash flow projection only 5 cash flow projection scenario that did not pass the test either the cash still minus after 3 years the business running or did not surpass the minimum requirement of NPV and IRR. The sensitivity analysis that included in economic feasibility will test the effect of NPV and IRR if the demand and the variable cost increased and decreased by 10% and 20%. After the economic feasibility tested to the remaining 11 cash flow projection, the optimal cash flow projection that still can be executed in the real world only 9 scenarios. The recommendation for new bakery product in Bandung must consist of the combination of the attribute that has Rp 5000 - Rp 7500 price range and sold in a supermarket or mini market. Also, the company must be sold the product at Rp 7500 price range and in 11 location to survive the bakery industry in Bandung.